High-concentrate diets with fibrous by-products for feedlot Nellore heifers - Van Cleef, Eric H. C. B.; De Oliveira, Priscila S. N.; Galati, Rosemary Lais; Ferreira, Daniel S. [UNESP]; Santos, Viviane C. [UNESP]; Homem Junior, Antonio Carlos [UNESP]; Pereira Junior, Sergio Antonio G. [UNESP]; Pardo, Rene Mauricio P.; Ezequiel, Jane Maria B. [UNESP] (Acad Brasileira De Ciencias, 2021)
The objective of this study was to evaluate high-concentrate diets and two energy sources on intake, performance and meat quality parameters of feedlot Nellore heifers. Twenty-eight heifers (200 +/- 22.5 kg BW) were randomly assigned to four treatments in a 2x2 factorial arrangement: two concentrate levels (70 and 80%) and two energy sources (corn and corn germ meal). At the end of day 112, heifers were slaughtered. There was no interaction (P>0.05) of concentrate levels and energy sources for dry matter intake, unlike crude protein (CP) and neutral detergent fiber (NDF) intakes. The concentrate level of 80% and corn, allowed the highest CP (1.17 kg/day) and NDF (4.05 kg/day) intakes. Final BW (P<0.05) and daily gain (P<0.01) were influenced just by energy source. The carcass composition represented by muscle and fat was affected by concentrate level (P<0.05). Treatments affected (P<0.01) carcass fat deposition, global preference and texture of Longissimus muscle (P<0.05). It was concluded that high proportions of concentrate containing corn as energy source provided the best performance in heifers, and that the total replacement of corn with corn germ meal in high-concentrate diets is not recommended for performance Nellore heifers, but provided good sensory quality to the meat.
Keywords: energy sources; fiber; intake; performance; starch